A importância do design na indústria do calçado português - Barbosa, Maria Manuela Tuna, 1989- (2015)
Over the years we noted the importance of design in different areas, and this discipline is of great importance for the development of products and / or innovative systems, defends itself ever more the importance of this area in different industries as a problem solver. This paper focuses on the Portuguese Footwear Industry and the influence that design has in it. Show how the Design is present and how it is important within an innovative industry, different, flexible, consistent, such as the Portuguese Footwear Industry that is the purpose of this work. The National Footwear Industry, achieved a remarkable national positioning in recent decades, from little-known to one of the most booming at national level and having become competitive among the top global counterparts industries. In this work is present an analysis of the route of the Portuguese footwear, taking in account a large number of strategies implemented by the sector, the changes obtained and the desired evolution, showing where and how the Design performed over the years. The Circuit of Culture of Design, of Paul du Gay and Stuart Hall, was introduced in this work in order to make a parallelism between the Portuguese footwear industry and the Design, to show how this discipline is present within the industry and how it relates between identity, production, consumption and regulation of a productive sector